(untitled) (Eurasian Journal of Religious Studies, 2024)
This article examines the topic of charity based on “Waqf” funds in the pages of Kazakh publications of the 20th century. All documentary information used in the scientific article to discuss this issue quoted from the "Kazakh" newspaper, "Sholpan" magazines of the 20th century. Scientific findings on the concept, purpose and scientific methodical foundations of waqf reflected in the articles published on the pages of the publication. The limited number of scientific articles and research papers on the mentioned topic in domestic research determines the relevance of the mentioned issue and the need to systematize this area. Today, in the Republic of Kazakhstan, the topic of waqf, which regulates the Islamic economy, including private property relations, is one of the new directions. The ways of development of Islam, its influence on ideology, social life and economy discussed at different levels. Islamic economy, including the concept of waqf, is a form of new property rights and new services for the Kazakh society. From a practical point of view, all aspects of private property determined by the government within the framework of the law. Key words: property rights in Islam, Kazakh newspaper, charity, waqf, zakat.